(untitled) - Ayuningtyas Y. Hapsari; Irma Rianti; Sigit Ramadhan; Shoffa A. Fauziyyah; Savira A. Putri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Many people think that covid-19 is not a serious disease, so they ignore health protocols. High number of positive cases in Indonesia is due to many people who do not implement health protocols according to government recommendations or there are still some people who ignore health protocols which can harm other people who always try to implement health protocols properly. This study aims to see how the lifestyle of the new adapted habitat community, knowledge, dinescape and repurchase intention at a restaurant in Bandung City and to see the influence of lifestyle, knowledge and dinescape on repurchase intentions at a restaurant in Bandung, both partially or simultaneously. This research uses descriptive verification method. The sample used is the people of Bandung City. The questionnaires were distributed evenly in five regions using path analysis and hypothesis testing. Based on the results of the study it can be ignored that lifestyle, knowledge and data have an effect on repurchase intentions at one of the restaurants in Bandung, either partially or simultaneously.